Impact of WHO Labor Care Guide on reducing cesarean sections at a tertiary center: an open-label randomized controlled trialAJOG Global Reports at a Glance - Divya Pandey, MS; Rekha Bharti, MD; Anjali Dabral, MD; Zeba Khanam, MD (Elsevier, 2022)
BACKGROUND: The World Health Organization Labor Care Guide was introduced in December 2020 to implement World Health Organization (WHO) guidelines on intrapartum care for a positive childbirth experience. OBJECTIVE: This study aimed to determine the effect of the WHO Labor Care Guide on labor outcomes, especially in reducing primary cesarean deliveries, and its acceptability by healthcare providers. STUDY DESIGN: This open-label randomized control trial was conducted from September 2021 to December 2021 on 280 low-risk antenatal women admitted for delivery at a busy tertiary care institute in North India. After informed consent, women were allocated into the study and control groups. Labor monitoring was performed using the WHO Labor Care Guide in the study group and the World Health Organization-modified partograph in the control group. Women who had a cesarean delivery in the latent phase of labor were excluded from the study. The primary outcome was mode of delivery, whereas the secondary outcomes were duration of active labor, maternal complications (postpartum hemorrhage and puerperal sepsis), duration of hospital stay, Apgar score at 5 minutes, and neonatal intensive care unit admission. The labor outcomes in both groups were compared. In the study group, the acceptability, difficulty, and satisfaction levels of the users were assessed using a 5-point Likert scale. The "learning curve" for the use of the Labor Care Guide (LCG) was determined. SPSS software (version 21.0; IBM Corporation, Chicago, IL) was used for statistical analysis. RESULTS: After excluding women who underwent cesarean delivery in the latent phase, 136 women in the study group and 135 women in the control group were observed for labor outcomes. The cesarean delivery rate was 1.5% in the study group vs 17.8% in the control group (P=.0001). The duration of the active phase of labor was significantly shorter in the study group than in the control group (P<.001). The 2 groups were similar in terms of maternal complications, duration of hospital stay, and Apgar score. The learning curve took average levels of 6.50 and 2.25 Labor Care Guide plots to shift from "very difficult" to "neutral" and "neutral" to "easy," respectively. After an initial learning curve, acceptability and satisfaction levels were found to be high in the WHO Labor Care Guide users. CONCLUSION: The WHO Labor Care Guide is a simple labor monitoring tool for the reducing primary cesarean delivery rate without increasing the duration of hospital stay and fetomaternal complications.